Effects of hydrodynamic conditions and temperature on polar organic chemical integrative sampling rates. (8th August 2018) - Djomte, Valerie Toteu; Taylor, Raegyn B.; Chen, Sunmao; Booij, Kees; Chambliss, C. Kevin
Abstract: The effects of changing hydrodynamic conditions and changing temperatures on polar organic chemical integrative sampler (POCIS) sampling rates ( R s ) were investigated for 12 crop protection chemicals. Exposure concentration was held constant in each laboratory experiment, and flow velocities were calculated from measured mass transfer coefficients of the water boundary layer near the surface of POCIS devices. At a given temperature R s generally increased by a factor of 2 to 5 between a stagnant condition and higher flow velocities (6–21 cm/s), but R s for most compounds was essentially constant between the higher flow velocities. When temperature was varied between 8 and 39 °C for a given flow condition, R s increased linearly. In general, R s increased by a factor of 2 to 4 and 2 to 8 over this temperature range under flow and stagnant conditions, respectively. An Arrhenius model was used to describe the dependence of POCIS sampling rates on temperature. Adjustments of Rs for temperature did not fully explain observed differences between time‐weighted average concentrations of atrazine determined from POCIS and from composite water sampling in a field setting, suggesting that the effects of other competing factors still need to be evaluated. Environ Toxicol Chem 2018;37:2331–2339. © 2018 SETAC